DFT investigation of the thermodynamics and mechanism of electrophilic chlorination and iodination of arenes; Journal of Molecular Modeling; Vol. 17, iss. 11 - Filimonov V. D. Viktor Dmitrievich; Poleshchuk O. Kh. Oleg Khemovich; Krasnokutskaya E. A . Elena Aleksandrovna; Frenking G. Gernot (2011, 2011)
Title screen